Private participation in the provision of water services : alternative means for private participation in the provision of water services - Lee, Terence R. (UN ECLAC SantiagoCL, 1997)
Focuses on the alternatives available for the privatization of water services and the experience of governments with these different alternatives. Discusses divestiture, the various forms of franchising, such as contracting out, management contracts, lease contracts and concessions, including the many 'build, operate amd transfer' arrangements, and joint public-private arrangements.